Avaliação da implantação de um time TPM: estudo de caso em cervejaria - Padovan, Bruna Caroline (2013)
The objective of this study is to evaluate the deployment of a team of TPM (Total Productive Maintenance in a brewery in the city of Ponta Grossa / PR. For this, we carried out an applied research through a case study in a brewery in town Ponta Grossa, PR. Initially, we analyzed the performance indicators of the company, mapping and identifying critical areas of action for the implementation of a TPM team. was verified among all sectors, the indicator with the highest rate of accidents and the sectors most likely to their occurrence were the Potting and Quality Control (QC), respectively, with the former already had a team in action. Later, through specific studies in Laboratory Quality Control, he was by the number of risks that area more vulnerable to accidents was the raw Material, Packaging and Packaging Materials. findings of this study indicate that the implementation of TPM was positive for the sector studied.